Iktibar umat Islam pasca al-Muwahhidun menurut Malik Bennabi: Lessons to the Muslim Post al-Muwahhidun According to Malik Bennabi - Abdul Razak, Abdul Qayuum; Ab Halim , Adlina; Ahmad, Zaid; Othman, Normala (Journal of Al-Tamaddun, 2022)
This paper aims to explore the ideas and thoughts of Malik Bennabi on the issue of civilization, especially the Islamic world. At the same time, this article will identify ideas that can be taken as lessons from the ‘post-al-Muwahhidun’ according to Malik Bennabi. Besides that, it also discusses the situation of Muslims after the fall of the caliphate of al-Muwahhidun which he referred to as colonisabilite who have lost ‘spirit’ and ‘idea’. This situation is described by Malik Bennabi as in a state of stagnation for a long time. This paper uses the method of content analysis through inductive and deductive forms from Malik Bennabi’s books as primary sources and other related documents. In addition, historical analysis was also conducted to strengthen the arguments and findings of the article. The study divides Malik Bennabi’s analysis of the issue of ‘civilization’ into four main lessons. First, the issue raised is that Muslims need to understand the current phase of Muslims in the context of the cycle of civilization, second; reconstructing the culture, third the importance of education, science and ideas and fourth Muslims need to respond to the call of religion. The issues raised are seen as significant and relevant to the development and situation of Muslims today. Together, it needs to be understood and internalised to regenerate the glory and strength of Islam as achieved in the past.